The water quality of the Upper Citarum: Applying the overall index of pollution, Said-WQI, and pollution index methods - Mariana Marselina; Nurul Aulia Rahmi; Siti Ai Nurhayati (Heliyon)
Water is a crucial natural resource, integral to sustaining human life and environmental equilibrium. However, water quality remains a critical issue issue due to prevailing contamination. While river water is a primary source of raw drinking water, much of it, such as Indonesia's Citarum River in West Java, has been polluted. While studies in Indonesia using the Water Quality Index (WQI) are limited, various measurement methods have been developed globally to evaluate water quality. This research compares three methods – the Overall Index of Pollution (OIP), Said-WQI method, and Pollution Index (PI) – to assess the water quality of Upstream Citarum River. The research utilized both primary and secondary data derived from Citarum River samples. Additionally, analytical tools including Microsoft Excel, Geographic Information System (GIS), and SPSS, were used for data processing, rainfall analysis, and statistical testing, respectively. Results from four river-monitoring points indicated average values for key parameters such as biochemical oxygen demand, dissolved oxygen (DO), and total and fecal coliform, falling below established quality standards. WQI measurements revealed variable degrees of pollution in the Upstream Citarum River according to the method used. The OIP and Said-WQI methods categorized the river's status as ranging from ‘good’ to ‘poor’, while the PI method classified it from ‘mildly polluted’ to ‘severely polluted’. Seasonal analysis of wet and dry months using secondary data revealed OIP index values ranging from 3.71 to 11.20, classifying water quality as ''poor'' to ''moderate''. The Said-WQI method yielded values between 0.67 and 2.34, indicating ''poor'' to ''good'' quality, while the PI method produced values from 4.15 to 8.13, denoting “moderately polluted” to “heavily polluted” conditions. Spatial analysis showed that upstream conditions were better than downstream conditions. The OIP index ranged from 3.71 upstream to 11.20 downstream with a classification of “poor” to “good”. The Said-WQI index ranged from 0.67 upstream to 2.34 downstream, classified as – “poor” to “good”. Similarly, the PI index ranged from 4.15 upstream to 8.13 downstream, indicating “moderately polluted” to “severely polluted” conditions. These findings from secondary data were corroborated by primary field sampling results. This study successfully evaluated the water quality of the Upper Citarum River by comparing measurement data with established standards across various locations and time periods. Furthermore, it conducted a comparative analysis of the differences between the three indices, focusing on parameters, sub-index transformations, weighting, and aggregation processes.